Public psychiatric services: job satisfaction evaluation - Ishara,Sergio (2008)
OBJECTIVE: To investigate the satisfaction of health-care professionals in inpatient and outpatient psychiatric hospitals of a Brazilian medium-sized city. METHOD: The study evaluated 136 health-care professionals from six hospitals; of which two were outpatient hospitals, two general hospitals, and two psychiatric hospitals. All professionals answered the Brazilian Mental Health Services' Staff Satisfaction Scale. RESULTS: An average satisfaction score of 3.26 was observed, which is situated between indifference (level 3) and satisfaction (level 4). Factors "service quality" (3.48) and "relationships at work" (3.48) showed higher scores compared to "service participation" (3.20) and "work conditions" (2.97) (p < 0.001). The female patient unit in the psychiatric hospital presented lower satisfaction scores (p < 0.001). Satisfaction was higher in the category "technicians" compared to "physicians" and "nurses" (p = 0.004). Moreover, day workers reported higher satisfaction compared to night workers regarding "service quality" and "service participation" (Student's t, p = 0.01 and p = 0.007). DISCUSSION AND CONCLUSION: Results show an intermediate level between indifference and satisfaction with services, with higher scores regarding care provided to the patients. Comparisons among the studied facilities revealed the numerous factors involved in determining one's satisfaction. They suggest advancements and reform measures likely to occur in the region's psychiatric health-care services. Monitoring satisfaction proved useful in predicting service quality improvements.